Analisis Implikatur Percakapan dalam Novel Forgulos Karya Aveus Har serta Implikasinya terhadap Pembelajaran Bahasa Indonesia di SMP - Dini Ulfiana; Etika Widi Utami; Erwan Kustriyono (Edu Berkah Khatulistiwa, 2026)
The ability to understand implied meaning is essential in language learning, as communication does not always convey meaning explicitly. This study aims to identify the forms and types of conversational implicature in the novel Forgulos by Aveus Har and to explain its relevance to Indonesian language learning at the junior high school level. This research employs a descriptive qualitative approach, with data derived from utterances in the novel Forgulos. Data were collected using observation and note-taking techniques, while data analysis was conducted using the matching method with the determining element sorting technique. The results show that there are two types of conversational implicature, namely 20 instances of conventional implicature and 10 instances of nonconventional implicature. These implicatures function to convey implied meanings, deepen character development, and support the progression of the plot. The findings are relevant to Indonesian Language Learning Outcomes in Phase D and can be utilized as alternative teaching materials to enhance students’ ability to interpret both explicit and implicit meanings in literary texts.